DASAR PENGEMBANGAN LEMBAR KERJA ANAK MODEL PEMBELAJARAN STEM UNTUK KELOMPOK B SUB TEMA BENDA-BENDA ALAM - Widya, Anggi; Rahman, Taopik; Mulyana, Edi Hendri (Universitas Pendidikan Indonesia (UPI), 2021)
This research is a research on developing children's worksheets for STEM learning models for group B sub-theme of natural objects. This research is a solution to problems regarding the demands of 21st century education which requires students to have 21st century skills, namely 4C skills (communication, collaboration, critical thinking, creative). It is expected that students are able to have comprehensive STEM knowledge and skills through the learning process at school. The purpose of this study was to develop children's worksheets for STEM learning models for group B sub-theme of natural objects. In particular, this research has the objectives of 1) describing the basic learning needs using the STEM learning model children's worksheets for group B sub-theme of natural objects; 2) develop and describe the design for developing children's worksheets for the STEM learning model for group B with the sub-theme of natural objects; 3) describe the trial and final product of the development of the STEM learning model children's worksheet for group B with the sub-theme of natural objects. Researchers developed this product based on the Education Design Research (EDR) steps from Mckenny Reaves (2012). These steps include 1) Analysis and Exploration; 2) Design and Construction; 3) Evaluation and Reflection. Researchers conducted research up to stage 1, namely the analysis and exploration stage. This study involved the teacher as the subject of the study. Data collection techniques used by researchers are interviews and documentation. The results of this study are the STEM learning model is still not widely used, so the use of the STEM learning model children's worksheet for group B sub-theme of natural objects has not been used.Penelitian ini merupakan penelitian pengembangan lembar kerja anak model pembelajaran STEM untuk kelompok B sub tema benda-benda alam. Penelitian ini merupakan solusi terhadap permasalahan mengenai tuntutan pendidikan abad 21 yang mengharuskan siswa memiliki keterampilan abad 21 yaitu keterampilan 4C (communication, collaboration, critical thinking, creative). Diharapkan siswa mampu memiliki pengetahuan dan keterampilan STEM secara menyeluruh melalui proses pembelajaran di sekolah. Tujuan penelitian ini untuk mengembangkan mengembangkan lembar kerja anak model pembelajaran STEM untuk kelompok B sub tema benda-benda alam. khususnya penelitian ini memiliki tujuan yaitu 1) mendeskripsikan dasar kebutuhan pembelajaran menggunakan lembar kerja anak model pembelajaran STEM untuk kelompok B sub tema benda-benda alam; 2) mengembangkan dan mendeskripsikan rencangan pengembangan lembar kerja anak model pembelajaran STEM untuk kelompok B sub tema benda-benda alam; 3) mendeskripsikan uji coba dan produk akhir rancangan pengembangan lembar kerja anak model pembelajaran STEM untuk kelompok B sub tema benda-benda alam. Peneliti mengembangkan produk ini berpedoman pada langkah langkah Education Design Research (EDR) dari Mckenny Reaves (2012). Langkah-langkah tersebut diantaranya 1) Analysis and Exploration; 2) Design and Construction; 3) Evaluation and Reflection. Peneliti melakukan penelitian sampai pada tahap 1 yaitu tahap analysis and Exploration. Penelitian ini melibatkan guru sebabagi subjek penelitian. Teknik pengumpulan data yang digunakan peneliti adalah wawancara dan dokumentasi. Hasil dari penelitian ini adalah model pembelajaran STEM masih belum banyak digunakan, , sehingga penggunaan lembar kerja anak model pembelajaran STEM untuk kelompok B sub tema benda-benda alam belum digunakan.